Avolition Characterizes the Chronic Fatigue Experienced in Quiescent Inflammatory Bowel Disease - Tristan Gabriel-Segard; Margherita Boltri; Mathilde Barrau; Catherine Massoubre; Stéphane Paul; Xavier Roblin (Biomedicines)
Background and Aims: Avolition is a symptom responsible for a high burden in patients suffering from psychiatric diseases. It refers to a motivation loss for initiating and maintaining goal-directed activities, often called fatigue by patients. Fatigue is a widespread complaint of patients suffering from inflammatory bowel disease (IBD), significantly impacting patients’ well-being, even during the quiescent stage of the disease. We here address the hypothesis that fatigue experienced by IBD patients is associated with motivational impairment. Methods: Patients presenting IBD (n = 110) in a quiescent stage of Crohn’s disease (CD) (n = 60) and ulcerative colitis (UC) (n = 50) were enrolled and classified following their declared experience of fatigue (n = 58) or not (n = 52). Patients were phenotyped using self-administered scales for fatigue experience, bowel disease disability, quality of life and mental health symptoms. Results: The self-administered negative symptoms scale scores identified avolition as a specific feature of fatigue experience: fatigued vs. no-fatigue in the CD group (3.806 vs. 2.103; p = 0.003) and in the UC group (2.815 vs. 1.174; p = 0.003). This difference is independent of current depressive disorder and previous history of depressive disorder. Avolition associates and correlates with the experience of fatigue (r = 0.49) in multivariate analysis. Conclusions: To tackle the question of fatigue in IBD, research should consider investigating the biological mechanisms implicating intestinal physiopathology of IBD in the impairment of brain structure involved in motivation. This may open new fields for treatment in targeting structures of the brain reward system.